Optical and structural characterization of Si/SiGe heterostructures grown by RTCVD - Ferrari, Michele; Strunk, Horst Paul; Christiansen, Silke; Sidiki, T.; Chabert, S.; de Boer, W.B.; Sotomayor, Torres (Thin Solid Films, 2000)
The effect of interface potential fluctuations of a Si/SiGe multiple quantum well structure upon the low temperature exciton luminescence is studied. A possible exciton localization at such potential fluctuations, with a lateral period of 9-12 nm, is observed as a blue shift with increasing excitation power in the low temperature photoluminescence. Moreover, annealing the sample at temperatures well below the growth temperature leads to the formation of striations with a period of several micrometers along the 011 direction. To clarify whether or not a metallic decoration of misfit dislocations is needed to observe D 1-line photoluminescence (PL) emission, annealing was performed in two different ways. Only in the case of annealing in direct contact with a metal, D 1-line emission was observed in photoluminescence experiments.
UnivIS-Import:2015-03-09:Pub.2000.tech.IW.LM.optica_1